An Exploratory Study Using Science eTexts With Students With Autism Spectrum Disorder. (June 2015) - Knight, Victoria F.; Wood, Charles L.; Spooner, Fred; Browder, Diane M.; O'Brien, Christopher P.
Supported electronic text (eText), or text altered to provide support, may promote comprehension of science content for students with disabilities. According to the Center for Applied Special Technology, Book Builder ™ uses supported eText to promote reading for meaning for all students. Students with autism spectrum disorder experience difficulty comprehending science content because of the extensive amount of background knowledge required in conjunction with difficulties understanding abstract and figurative language. Investigations on the most effective methods for reading comprehension and teaching science to this population are equally limited. In this pilot study, feasibility was supported in high levels of treatment fidelity and teacher- and student-reported satisfaction. A multiple probe across participants with an embedded ABCD design was used to evaluate various modifications of Book Builder ™ on measures of vocabulary, literal comprehension, and application questions. Considerations for students with ASD, limitations, and recommendations for future research conclude the article.